PERAN KEPEMIMPINAN PENDIDIKAN DALAM STRATEGI MANAJEMEN KEARSIPAN - Fatikha Aqsha Kamila; Ngishmatul Firdausiyyah; Rosidatun Nafisah; Siswadi (STKIP Subang, 2026)
This study aims to examine the role of educational leadership in archival management strategies within educational institutions. The method used is library research by analyzing various relevant literature sources, including books, scientific journals, and previous research findings. The results show that educational leadership plays a crucial role in formulating policies, managing archival systems, and promoting the use of technology in records management. Common problems in archival management include document accumulation, unstructured filing systems, and limited human resource competence. Therefore, effective and visionary leadership is required to develop systematic archival strategies, improve administrative staff competencies, and build an orderly administrative culture. In conclusion, educational leadership is the key factor in achieving effective, efficient, and accountable archival management in educational institutions. Keywords: educational leadership, archival management, educational administration, strategy, digital archiving